DEVELOPING PROFESSIONAL LEXICAL COMPETENCE AMONG FUTURE TEACHERS (Conferencea, 2022)
This article discusses the knowledge and skills in a competency-based approach in terms of gaining experience. In modern pedagogy, the development of culturally related lexical competencies among students is also discussed.